Long-term efficacy and safety of canakinumab in patients with mevalonate kinase deficiency: results from the randomised Phase 3 CLUSTER trial. (23rd September 2021) - Jeyaratnam, Jerold; Simon, Anna; Calvo, Inmaculada; Constantin, Tamas; Shcherbina, Anna; Hofer, Michael; Gattorno, Marco; Martini, Alberto; Bader-Meunier, Brigitte; Vastert, Bas; Levy, Jeremy; Dekker, Elise; et al.
Abstract: Objectives: To evaluate the long-term efficacy and safety of canakinumab in patients with mevalonate kinase deficiency during the open label extension (weeks 41–113) of the randomized controlled CLUSTER trial. Methods: During a 72-week period, patients received open-label canakinumab 150 or 300 mg, every 4 or 8 weeks. The disease activity was evaluated every 8 weeks using physician global assessment and counting the number of flares. Concentrations of CRP and serum amyloid A protein were measured. The safety was studied by determination and classification of observed adverse events. The safety and efficacy were analysed separately in three subgroups of patients receiving a cumulative dose of less than <35 mg/kg, ≥35 to <70 mg/kg or ≥70 mg/kg. Results: Of the 74 patients who started the CLUSTER study, 66 entered Epoch 4 and 65 completed it. During the 72-week period, 42 (64%) patients experienced no flares, while 13 (20%) had one flare, as compared with a median of 12 flares per year reported at baseline. Low physician global assessment scores were seen at the end of the study for all groups with >90% reporting minimal disease activity or none at all. Median CRP concentrations were consistently equal or lower than 10 mg/l, while median serum amyloid A concentrations remained only slightly above the normal range of 10 mg/l. The study showed no new or unexpected adverse events. Conclusion: Canakinumab proved effective to control disease activity and prevent flares in mevalonate kinase deficiency during the 72-week study period. No new safety concerns were reported. Trial registration: NCT02059291. https://clinicaltrials.gov .